Night Drawing: Re-writing Darkness in the Nocturnal Land/Cityscape - Meng, Chantal (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2022)
Night Drawing is an action that challenges perceptual habits—an embodied experience at the limits of the visible. Dealing with light at night is an urgent issue for a variety of social and cultural reasons and concerns the wider context of anthropogenic climate change. This paper deals with lighting conditions in the urban night on one hand and forms of cognition through drawing on the other. When it comes to artificial light at night, the foremost concerns include safety, light pollution, and the loss of darkness. However, the fact that darkness is also caused by and understood through artificial light is rarely discussed. Night Drawing aims to renegotiate long-standing assumptions about the benefits of urban nighttime lighting. This approach offers a challenge to the brighter the better idea and re-writes the appearance of nocturnal land/cityscapes. Night Drawing is a critical, innovative approach, a practice as a method to pay further attention to the representational power of the light at night. It aims at a technique of seeing in a new way—a re-examination and a new conception of urban darkness.